Solar Radiation Estimation Using Discriminate Analysis Algorithm for The Output Voltage of Photovoltaic Module. Issue 1 (May 2021) - Irwanto, M; Ismail, B.; Nisja, I.; Irwan, Y. M.; Alam, H; Baharudin, N H; Jufrizal,; Leow, W Z; Ahmad, S
Abstract: A study of solar radiation in one area is very important to decide the area is suitable or not to be constructed the generation of photovoltaic (PV) system. The solar radiation can be recorded using the equipment of solar power meter or weather station. But it is due to the limitation of equipment, maybe a technical error occurs on the equipment, thus the equipment has a problem to record the data of solar radiation or one area has no equipment of solar radiation recording. An estimation method of solar radiation is needed to solve the problem. This paper presents an estimation of solar radiation using discriminate analysis algorithm (DAA) that it is applied to the output voltage of PV module. The data of daily measured solar radiation, maximum and minimum temperature are obtained from Chuping Weather Station through the web of world weather online for the year of 2019. The maximum and minimum temperature are as predictor variables in the DAA to obtain the daily estimated solar radiation. The result of daily estimated solar radiation is applied to the output voltage of PV module and compared to the output voltage of PV module applied by the daily measured solar radiation using the statistical analysis, they are root mean square error (RMSE) and error percentage. The results show that the estimated and measured solar radiation have RMSE of 0.257 and error percentage of 1.649%. They indicate that the DAA is acceptable to estimate the solar radiation.